2017
DOI: 10.4028/www.scientific.net/msf.897.755
|View full text |Cite
|
Sign up to set email alerts
|

Bulk β-Ga<sub>2</sub>O<sub>3</sub> with (010) and (201) Surface Orientation: Schottky Contacts and Point Defects

Abstract: Electrical properties of Schottky contacts of high work-function metals (Pd, Au, and Ni) on (010) and (201) oriented β-Ga2O3 were investigated. Current-voltage characteristics reveal that all the contacts exhibit high rectifying behavior with ideality factors as low as 1.04. However, the reverse leakage currents were lower in the (010) samples compared to the (201) ones. Thermal admittance spectroscopy confirms a main charge carrier level to be at ~0.15 eV below the conduction band edge (Ec). Secondary ion mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The level labeled as E1 (here and in the literature) exhibits characteristics similar to those reported previously. 10,17,18 The properties of E2 observed in the HVPE sample are also consistent with the literature. 19 Both these levels are seen at low concentrations in our samples and are taken out of consideration in the rest of our analysis.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The level labeled as E1 (here and in the literature) exhibits characteristics similar to those reported previously. 10,17,18 The properties of E2 observed in the HVPE sample are also consistent with the literature. 19 Both these levels are seen at low concentrations in our samples and are taken out of consideration in the rest of our analysis.…”
Section: Methodssupporting
confidence: 89%
“…E-beam deposition of Ni was used to manufacture Schottky contacts that exhibited suitable properties for the DLTS characterization. 18 Circular Ni contacts with radii 100, 240, and 400 μm were deposited through a shadow mask on the wafers using e-beam evaporation. A stack of Ti/Al was applied to the back of the wafers to serve as an ohmic contact, also using e-beam evaporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A defect level with similar activation energy was found in homoepitaxial β ‐Ga 2 O 3 thin films fabricated by metal organic chemical vapor deposition or fabricated by plasma enhanced molecular beam epitaxy . In bulk samples, a defect level with this activation energy was not detected or found by computer simulations . This is a hint that this defect commonly occurs in epitaxial β ‐Ga 2 O 3 thin films.…”
Section: Resultsmentioning
confidence: 67%
“…In contrast, the (100) plane is nonpolar 18 and shows good convergence. Furthermore, experiment 19 showed that the dependence on different planes is not very notable. Therefore, we construct interfaces with ten-layer (100) oriented b-Ga 2 O 3 and four-layer metal atoms.…”
Section: Methodsmentioning
confidence: 96%